Transient analysis of a near-zero energy building with green hydrogen production integrated with energy storage systems - Haddad, Masoud; Javani, Nader (ELSEVIER, 2024)
The current study highlights the potential of hybrid renewable energy systems in mitigating CO2 emissions for a near-zero energy building. A Python-based controller is used to manage the state of charge (SoC) of the lithium-ion battery. Two buildings are considered in the study. Once the SoC in the first building reaches 75 %, the system prevents overcharging and redirects the green electricity towards the hybrid system for hydrogen production. To compare the role of a hybrid system in which a fuel cell is used to supply the required energy for electric load and electrolyzer demand, a diesel generator is considered for the same energy demands. The hybrid system achieves a 56.14 % reduction in diesel fuel consumption, leading to an annual decrease of 33.860 tons of CO2 emissions. Economic analysis reveals that while the cost of the diesel mode is calculated to be 96 % higher than the hybrid mode, the CO2 emissions in the hybrid mode will be 56.14 % lower than the full diesel mode. Additionally, the system's total annual hydrogen production is 7582.74 kg, with a maximum production rate of 15.52 m(3)/hr at 1.3 bar pressure. Despite higher initial costs, hybrid systems effectively address the challenge of CO2 emissions compared to conventional systems. The results underscore the necessity of hybrid systems for achieving significant reductions in fossil fuel consumption, presenting a sustainable solution for future energy needs.
Keywords: Photovoltaic panels; Solar energy; Exergy efficiency; Battery energy storage; Near-zero energy building; PHOTOVOLTAIC SYSTEM; OPTIMIZATION; BATTERY; Construction & Building Technology; Engineering